Renal denervation does not affect hypertension or the renin-angiotensin system in a rodent model of juvenile-onset polycystic kidney disease: clinical implications - Sheran Li (Nature Portfolio, 2021)
Abstract We examined the effect of total and afferent renal denervation (RDN) on hypertension and the renin-angiotensin system (RAS) in a rodent model of juvenile-onset polycystic kidney disease (PKD). Lewis Polycystic Kidney (LPK) and control rats received total, afferent or sham RDN by periaxonal application of phenol, capsaicin or normal saline, respectively, and were monitored for 4-weeks. Afferent RDN did not affect systolic blood pressure (SBP) determined by radiotelemetry in either strain (n = 19) while total RDN significantly reduced SBP in Lewis rats 4-weeks post-denervation (total vs. sham, 122 ± 1 vs. 130 ± 2 mmHg, P = 0.002, n = 25). Plasma and kidney renin content determined by radioimmunoassay were significantly lower in LPK vs. Lewis (plasma: 278.2 ± 6.7 vs. 376.5 ± 11.9 ng Ang I/ml/h; kidney: 260.1 ± 6.3 vs. 753.2 ± 37.9 ng Ang I/mg/h, P < 0.001, n = 26). These parameters were not affected by RDN. Intrarenal mRNA expression levels of renin, angiotensinogen, angiotensin-converting enzyme (ACE)2, and angiotensin II receptor type 1a were significantly lower, whereas ACE1 expression was significantly higher in the LPK vs. Lewis (all P < 0.05, n = 26). This pattern of intrarenal RAS expression was not changed by RDN. In conclusion, RDN does not affect hypertension or the RAS in the LPK model and indicates RDN might not be a suitable antihypertensive strategy for individuals with juvenile-onset PKD.